Temporal and between-site variation in helminth communities of bank voles (Myodes glareolus) from N.E. Poland. 1. Regional fauna and component community levels - Behnke, Jerzy M.; Bajer, Anna; Harris, Philip D.; Newington, L.; Pidgeon, E.; Rowlands, G.; Sheriff, C.; Kulis-Malkowska, K.; Sinski, Edward; Gilbert, Francis; Barnard, C.J. (Cambridge University Press, 2008)
Helminth infections were studied in bank voles (Myodes glareolus) from 3 woodland sites in N.E. Poland in the late summers of 1999 and 2002, to assess the temporal stability of derived statistics describing the regional helminth fauna and component community structure, and spatial influence on the latter. Regional helminth fauna changed dramatically between the two years, primarily due to a fall in the abundance of Syphacia petrusewiczi but was partially compensated for by an increase in Mesocestoides lineatus and Cladotaenia globifera. It was dominated by nematodes overall, but more so in 1999 than in 2002 when larval cestodes were more frequent. Most derived parameters for component community structure varied considerably between sites and the two surveys, the hierarchical order for sites not being maintained between surveys. They were susceptible to the disproportionate influence of three relatively rare, unpredictable species with the greatest overall aggregated distribution among hosts. Jaccard’s similarity index was less influenced by the rare species, showing greater stability between sites and across years. In conclusion, temporal variation confounded any site-specific characteristics of the summary measures quantified in this study and their usefulness is therefore restricted to the years in which the surveys were conducted.